2018
DOI: 10.18001/trs.4.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Menthol Glucuronide as a Biomarker of Acute Menthol Inhalation

Abstract: Objectives Menthol is often added to cigarettes and e-cigarette solutions for its cooling and anti-irritant effects, and may contribute to development of nicotine dependence, particularly in vulnerable populations such as adolescents, and among African Americans. Menthol is rapidly metabolized to menthol glucuronide (MG) with little or no unconjugated menthol measurable in venous blood. Human challenge studies of the effects of inhaled menthol, and of its interactions with nicotine, would benefit from a quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…Participants took six inhalations, one every 15 s, over 90 s just prior to each of the three infusions. As reported elsewhere, this procedure resulted in highly significant, dose-dependent increases of venous plasma menthol glucuronide (a biomarker of menthol exposure) after inhalation that was proportional to the menthol solution concentrations inhaled by our study sample (Jatlow et al, 2018).…”
Section: Drugs Menthol Administration Each E-liquid (Prepared By Pacesupporting
confidence: 73%
“…Participants took six inhalations, one every 15 s, over 90 s just prior to each of the three infusions. As reported elsewhere, this procedure resulted in highly significant, dose-dependent increases of venous plasma menthol glucuronide (a biomarker of menthol exposure) after inhalation that was proportional to the menthol solution concentrations inhaled by our study sample (Jatlow et al, 2018).…”
Section: Drugs Menthol Administration Each E-liquid (Prepared By Pacesupporting
confidence: 73%
“…Plasma cotinine and 3-hydroxycotinine (3HC) and nicotine, were measured employing LC/MS/MS at session baseline and used to compute the nicotine metabolite ratio (NMR:3HC/cotinine), a marker of nicotine clearance which impacts heaviness of smoking and subjective nicotine effects. 32,33 Menthol glucuronide, a menthol metabolite, 34,35 also assayed by LC/MS/MS in plasma, was measured at baseline and after each block (Figure 1). Table 1).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Furthermore, following menthol cigarette smoking, increases in plasma MG concentrations have also been demonstrated ( Hsu et al, 2017 ). In a prior study, we showed that the AUC values of plasma MG concentrations increase proportionally to the concentration of menthol in the e-liquid ( Jatlow et al, 2018 ). In this study, we demonstrate changes in plasma MG concentrations following inhalation of e-cigarettes with different menthol concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, increases in plasma MG concentrations have been documented following menthol cigarette smoking, also called the “menthol boost” ( Hsu et al, 2017 ). We have also reported that the area under the curve (AUC) values of plasma MG concentrations following e-cigarette use are proportional to the menthol concentrations in the e-liquid ( Jatlow et al, 2018 ). To our knowledge, previous studies have not examined whether plasma MG levels serve as a biomarker for the acute subjective and physiological effects of menthol-flavored tobacco products.…”
Section: Introductionmentioning
confidence: 99%